Client Retention in Community Treatment: Completer and Noncompleter Experiences of an Individualized, Needs-Based Partner Abuse Intervention Program - Pearson, Dominic A. S. (Journal of interpersonal violence, 2022)
There has been increased interest in the subjective experiences of participants of community partner abuse intervention programs (PAIPs). In the context of high attrition rates, qualitative research is needed to understand the factors associated with sustained engagement and dropout. Using a community nonmandated PAIP, the current study is a rare investigation of the experiences of both completers and noncompleters. We explored the differences between completers? and noncompleters? perceptions of the treatment process, the reasons for sustained program engagement, and the perceived outcomes of treatment. Semi-structured interviews were completed with 14 participants: nine completers and five noncompleters. The majority of participants were referred by children?s social care and were unemployed at the time of interview. The interviews were conducted by research staff independent from the treatment-providing organization. Three themes emerged from the data: (a) Treatment as Challenging Yet Enlightening, (b) the Importance of a Well-timed and Safe Therapeutic Environment, and (c) Improved Emotional Self-Management Due to Treatment. Results highlighted how structured individualized sessions, underpinned by a strong therapeutic alliance with facilitators, helped participants increase their interpersonal problem-solving and communication skills. The study reinforced the importance of developing a therapeutic alliance and providing structured individualized treatment characterized by flexibility and accessibility. Noncompletion was perceived as related to known risk factors and treatment readiness. Therefore, it may be beneficial to employ screening measures to monitor these factors. Future research should use larger, more diverse samples to further investigate subjective experiences of PAIP completers and, particularly, noncompleters to enhance the limited literature in this area.